Laminated core and method for manufacturing laminated core
By alternately stacking electromagnetic steel plates and adhesive insulating films under low temperature and low pressure conditions, the problems of automation difficulties and production scale in lamination core manufacturing are solved, and an efficient and simplified manufacturing process is achieved.
Patent Information
- Application Number
- CN202380062199.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-08
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing laminated iron core manufacturing technology is difficult to automate when laminating the outer mold, resulting in reduced productivity; while when laminating the inner mold, high-temperature heating and cooling require a long time or a large cooling mechanism is required, resulting in difficulty in scale production.
The electromagnetic steel plate and the adhesive insulating film are alternately laminated, and heated and pressurized under low temperature (60°C to 200°C) and low pressure (3.0MPa or less) to form a laminated core. This method does not require special equipment with high temperature and high pressure, simplifying the manufacturing process.
The formation of high-strength laminated cores under low temperature and low pressure conditions is achieved, which simplifies the manufacturing device and improves production efficiency and scale-up capabilities.
Smart Images

Figure CN119816905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated core and a method for manufacturing a laminated core. This application claims priority based on Japanese Patent Application No. 2022-143134 filed in Japan on September 8, 2022, and the contents are incorporated herein by reference. Background Art
[0002] In recent years, the trend of reducing CO2 has been accelerating around the world, and the application of motors (rotating electrical machines, electric motors) that do not emit CO2 when driven has been expanding in various fields, including automobiles. In this trend, motors are required to be more energy-efficient and have higher output than ever before.
[0003] As a laminated body manufacturing technology for laminated cores used in motors, there are known technologies using riveting and laser fastening. Laminated cores manufactured using these laminated body manufacturing technologies have iron loss caused by conduction from the fastened parts, so this iron loss is one of the factors that hinder power saving and high output. Recently, the development of laminated body manufacturing technology for laminated cores using adhesives that focuses on reducing iron loss is being promoted.
[0004] Regarding the laminated body manufacturing technology of the laminated core using an adhesive, there are two methods: a method of applying an adhesive to an electromagnetic steel sheet and then punching the electromagnetic steel sheet, and a method of applying an adhesive to the electromagnetic steel sheet after punching the electromagnetic steel sheet. In addition, the assembly process of stacking the electromagnetic steel sheets after the adhesive coating is performed either inside a mold or outside a mold. Regarding these technologies, there are the following existing documents.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-274625
[0008] Patent Document 2: Japanese Patent Application Publication No. 2009-297758
[0009] Patent Document 3: Japanese Patent Application Publication No. 2022-000888
[0010] Patent Document 4: Japanese Patent Application Publication No. 2021-129453 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The technology of stacking electromagnetic steel sheets after adhesive coating outside the mold (see Patent Document 3 or Patent Document 4) is a technology of bonding adjacent electromagnetic steel sheets to each other by heating the stacked body at a high temperature, wherein the stacked body is taken out from the special jig after being temporarily fixed by applying high pressure to the plurality of electromagnetic steel sheets while being accommodated inside the special jig, or the stacked body fixed by the special jig. As such, the method of manufacturing the stacked body outside the mold is difficult to automate because it is accompanied by the fixing and taking-out process of the special jig, which is a factor in reducing productivity.
[0013] The technology of stacking electromagnetic steel sheets after adhesive coating in a mold (refer to Patent Document 1 or Patent Document 2) is different from the technology of stacking outside the mold. Since it does not include the process of taking out the stacked body, it is relatively easy to automate and has excellent productivity. However, when the stacked body is formed by bonding using high-temperature heating and then transported to the next process without rapid cooling, it takes a long time of about 3 to 4 hours for the temperature of the stacked body to drop to a temperature that can be transported. In addition, when rapid cooling is performed when transporting to the next process, a large-scale cooling mechanism for rapid cooling becomes necessary depending on the size of the stacked body, and the manufacturing device including the cooling mechanism is enlarged as a whole. As a result, the method of manufacturing a stacked body in a mold is difficult to mass-produce because the manufacturing takes time or the manufacturing device is enlarged, which becomes a factor in reducing productivity.
[0014] In view of the above problems of the prior art, the present application provides a laminated core and a method for manufacturing the laminated core that can be manufactured with high production efficiency.
[0015] Means for solving problems
[0016] The gist of the present invention is as follows.
[0017] (1) In a laminated core according to one aspect of the present invention, electromagnetic steel sheets and adhesive insulating films are alternately laminated, and after the adhesive insulating films are completely reacted, the tensile bonding strength in the lamination direction measured at 25° C. is 20 MPa or more.
[0018] (2) In the above (1), the uppermost electromagnetic steel sheet may have a convex portion protruding in the stacking direction.
[0019] (3) A method for manufacturing a laminated core according to one embodiment of the present invention is a method for manufacturing a laminated core formed by stacking a plurality of electromagnetic steel sheets, comprising the following steps: a punching step of punching an electromagnetic steel strip coated with an adhesive insulating film to form the electromagnetic steel sheets; a accommodating step of stacking the electromagnetic steel sheets and accommodating them in a mold after the punching step; a low-pressure bonding step of bonding adjacent electromagnetic steel sheets to each other while pressurizing the electromagnetic steel sheets in the mold to a surface temperature of 60°C to 200°C to form a laminated core; and a removing step of removing the laminated core from the mold after the low-pressure bonding step.
[0020] (4) In the above (3), the above low-pressure bonding step may include the following bonding promotion step: heating the temperature to 100°C to 160°C at a heating rate of 0.5°C / s to 10.0°C / s, and maintaining the above temperature for 20 seconds to 120 seconds.
[0021] (5) In the above (3) or (4), after the taking-out step, a reheating step of heating the laminated core to 160° C. to 250° C. may be included.
[0022] (6) In any one of the above (3) to (5), in the low-pressure bonding step, the electromagnetic steel sheet in the mold may be pressurized at 0.1 MPa or more.
[0023] Effects of the Invention
[0024] According to the present invention, a laminated core and a method for manufacturing the laminated core that can be manufactured with high production efficiency can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a three-dimensional diagram of a laminated core.
[0026] Figure 2 It is a plan view of the laminated core.
[0027] Figure 3 yes Figure 2 Cross-sectional view as viewed in the direction of A.
[0028] Figure 4 This is a table showing the relationship between the test specimens, test conditions, and test results of the tensile adhesion test. DETAILED DESCRIPTION
[0029] In order to improve the productivity of laminated cores, a manufacturing technology that stacks adhesive-coated electromagnetic steel sheets in a mold is appropriate. The manufacturing technology that stacks adhesive-coated electromagnetic steel sheets in a mold involves a process of heating the laminated body (laminated core) at high temperature and a cooling process, so the size of the manufacturing equipment becomes a problem.
[0030] The reason for heating the laminate at a high temperature is to obtain the required strength by using a thermosetting adhesive.
[0031] In order to promote the miniaturization or omission of manufacturing equipment, it is effective to use an adhesive having high strength when the laminate is completed without heating the laminate at a high temperature.
[0032] According to previous knowledge, in the manufacturing technology of laminated bodies, the following design is sometimes performed: the glass transition temperature Tg (temperature at which curing starts from a flexible state) of the adhesive used in the adhesive coating of the electromagnetic steel sheet is lowered (low Tg), and the curing reaction of the adhesive is promoted even at low temperatures to complete the curing early (to show the desired strength). However, in the case of a manufacturing technology that uses adhesive coating to stack electromagnetic steel sheets to manufacture laminated bodies, the curing reaction of the adhesive may be promoted by the transportation and storage of the manufactured laminated body, resulting in unintentional adhesion between materials called blocking. Therefore, in the conventional manufacturing technology of laminated bodies, temperature management, stacking amount management, etc. must be performed, which, as a result, becomes an obstacle to improving production efficiency.
[0033] In order to manufacture a laminate at a low temperature without utilizing low Tg, a tensile test was performed on the completed laminate in the stacking direction of the steel plates, and the tensile bonding strength in the stacking direction of the laminate required for the laminate used in the motor (hereinafter, the tensile bonding strength in the stacking direction is sometimes referred to as the tensile strength in the stacking direction) and the relationship between the temperature of the adhesive and the reaction status and strength were investigated. The tensile strength in the stacking direction is an evaluation index independently specified in the present application, and is the bonding strength of the laminate as a whole in the stacking direction (in the perpendicular direction relative to the bonding surface of the laminated plate with the adhesive) of a laminate formed by fastening a plurality of steel plates with an adhesive. In detail, the tensile strength in the stacking direction is the value obtained by dividing the load at which the laminate breaks when a tensile load is applied to the laminate in the stacking direction by the cross-sectional area of the cross section perpendicular to the stacking direction D of the laminate (the bonding area in one plate surface of the plate body constituting the laminate). On the other hand, the strength measured by the conventional method includes the tensile bonding strength of JIS K 6849:1994 and the tensile shear bonding strength of JIS K 6850:1999, but these are the bonding strengths of the adhesive alone. In addition, the tensile shear bonding strength is the bonding strength when a shear stress parallel to the bonding surface is applied. Here, the necessity of the tensile strength in the stacking direction specified in the present disclosure and the difference from the conventional method are described.
[0034] First, the resin used as an adhesive has a phase direction (orientation, anisotropy). Therefore, it is necessary to evaluate the direction that is considered necessary. However, as for the shear tensile strength that evaluates the tensile strength in the direction parallel to the bonding surface, it is insufficient in the case where stretching in the stacking direction is required as in this case. In addition, in the stretching of the test piece containing the resin, the bonding and phase properties at the interface between the resin and the steel plate are important. As for the tensile bonding strength of JIS K 6849:1994, it is not possible to evaluate the strength at the interface, which is insufficient.
[0035] Thus, the tensile strength in the stacking direction shows a strength different from the conventional strength. Furthermore, the tensile strength in the stacking direction found this time can be used to measure the adhesive strength of the entire stack in the stacking direction as follows.
[0036] The relationship between the tensile strength in the lamination direction and the temperature and reaction progress and strength of the adhesive was investigated, and the following findings were obtained.
[0037] 1) The tensile strength in the stacking direction required for the laminate used in the motor varies depending on the purpose of the motor. Even for motors used in electric vehicles (EVs), drones, or vacuum cleaners, the tensile strength in the stacking direction required for the laminate used in motors used at high rotation is high, which is higher than the bonding strength of general laminates fastened by rivets, which is 0.5 MPa, and is about 1 MPa.
[0038] 2) As the temperature rises, the adhesive cures in a process that progresses from a soft state (1) through a reaction-promoting state (2) to a reaction-completed state (3) (curing mechanism of the adhesive).
[0039] Emphasis is placed on the strength exhibited in the reaction completion state (3), and the adhesive is sometimes designed based on this strength. In contrast, in order to ensure the necessary strength, if the adhesive can ensure sufficient strength in the reaction promotion process (2) even without waiting for the reaction completion state (3), the necessary strength can be ensured without heating afterwards.
[0040] Based on this technical idea, it was discovered that if an adhesive is used that has a tensile strength in the stacking direction of 20 MPa or more, which is about 20 times the tensile strength in the stacking direction of 1 MPa required for a general motor stack at the end of the reaction, sufficient strength can be ensured in the reaction-promoted state (2) even without waiting for the reaction end state (3).
[0041] <<First Embodiment>>
[0042] The laminated core 10 according to the embodiment will be described.
[0043] Figure 1 It is a perspective view of the laminated core 10 . Figure 2 is a plan view of the laminated core 10 . Figure 3 yes Figure 2 Cross-sectional view as viewed in the direction of A.
[0044] like Figure 1 to Figure 3 As shown in , the laminated core 10 is formed by alternately laminating electromagnetic steel plates 1 and adhesive insulating films 2 in a laminating direction D. Moreover, after the complete reaction of the adhesive insulating film 2, the laminating direction tensile strength in the laminating direction D measured at 25°C is 20 MPa or more. It should be noted that the laminating direction tensile strength is more preferably 40 MPa or more. Here, the so-called complete reaction means that the curing rate reaches 100%, which means that a peak derived from heat generation is not generated in the DSC curve obtained by differential scanning calorimetry (DSC; Differential scanning calorimetry).
[0045] As described above, the tensile strength in the stacking direction is the value obtained by dividing the load at which the stack breaks when a tensile load is applied to the stack in the stacking direction by the cross-sectional area of the cross section perpendicular to the stacking direction D of the stack (the bonding area in one plate surface of the plate body constituting the stack). For example, it can be: Figure 1 A test body with the same cross section as that cut out from the laminated core 10 as indicated by the dotted line (for example, a test body in the shape of a cube with a length of 45.0 mm × a width of 3.6 mm × a length of 12.25 mm along the lamination direction D) is subjected to a tensile load along the lamination direction D by a tensile testing machine, and the maximum tensile load until the fracture is reached is divided by the cross-sectional area of the cross section of the test body perpendicular to the lamination direction D. Figure 1 As shown in , the test body is a laminated body formed by laminating an electromagnetic steel plate 1 and an adhesive insulating film 2. It should be noted that the electromagnetic steel plates constituting the test body are bonded to the entire surface by the adhesive insulating film. In addition, the fracture indicates that at least one of the adhesive insulating films formed between the plates constituting the laminated body is fractured. It should be noted that the tensile testing machine uses a tensile testing machine that can provide the No. 5 test piece described in JIZ Z 2241:2022 for the tensile test. The tensile testing machine uses, for example, a fully automatic tensile testing machine with a testing machine capacity of 100 kN.
[0046] It should be noted that the size of the test body is not limited to the above content, and the test body can be any test body cut out from the laminated core 10 in a manner that includes two or more layers of adhesive insulating films 2 (three or more layers of electromagnetic steel sheets 1 as adherends). In addition, there are no particular restrictions on the stacking direction of the test body and the cutting position in the plane perpendicular to the stacking direction. However, the test body is cut out from the laminated core 10 in a manner that does not include the convex portion 3 in the test body. At this time, it is a prerequisite to stack three or more electromagnetic steel sheets 1 in order to facilitate the implementation of the test and the frequency of stacking.
[0047] Thus, even at a relatively low temperature (60° C. to 200° C.), it is possible to exhibit the bonding strength (for example, 1 MPa) required for the laminated core 10 for a motor as a product.
[0048] Therefore, even if the electromagnetic steel sheets 1 are bonded to form a laminated body (laminated core) and are not further heated, a high-strength laminated core 10 can be manufactured. Therefore, the laminated core 10 can be taken out of the manufacturing device in a low-temperature state, and the mechanism for high-temperature heating and cooling in the manufacturing device can be simplified, so the manufacturing device of the laminated core 10 can be miniaturized. Therefore, a laminated core 10 that can be manufactured with high production efficiency and a method for manufacturing the laminated core 10 can be provided.
[0049] The electromagnetic steel sheet 1 is suitable for a high-efficiency motor, for example. The electromagnetic steel sheet 1 may be a non-oriented electromagnetic steel sheet (for example, original specification 25HX1300) having a yield strength of 394 MPa, low iron loss (13.0 W / kg or less), high magnetic flux density, and a thickness of 0.25 mm.
[0050] The adhesive insulating film 2 may be an adhesive applied in advance to the electromagnetic steel sheet 1 before the punching step described later.
[0051] The adhesive insulating film 2 can be applied to the surface of the electromagnetic steel sheet with a film thickness of 3 μm, for example. The adhesive insulating film 2 can be an adhesive resin containing a thermosetting resin as shown below. The mixing ratio of the thermosetting resin, organic components other than the thermosetting resin, inorganic components, etc. shown below is adjusted so that after complete reaction, the tensile strength in the stacking direction when measured at 25° C. is set to 20 MPa or more.
[0052] <Thermosetting resin>
[0053] If the thermosetting resin is specifically exemplified, cross-linked resins such as epoxy resin, thermosetting acrylic resin, polyurethane resin, unsaturated polyester resin, phenolic resin, melamine resin, urea resin, and thermosetting polyimide resin may be listed. In the present invention, these resins may be used alone or in combination of two or more.
[0054] (Epoxy resin)
[0055] Epoxy resin is a resin containing two or more epoxy groups, and is a resin that is three-dimensionally cured by cross-linking two or more epoxy groups present in the resin with an appropriate curing agent. Examples of epoxy resins containing epoxy groups include bisphenol-based (bisphenol A type, bisphenol F type, bisphenol AD type), naphthalene-based or Cardo-based epoxy resins.
[0056] (Thermosetting acrylic resin)
[0057] Examples of thermosetting acrylic resins include copolymers of acrylic acid esters or methacrylates and acrylic acid monomers having reactive functional groups such as hydroxyl, amino, N-methylol, N-alkoxymethylformamide, allyl, or epoxy groups. Specifically, examples include copolymers of methyl acrylate or methyl methacrylate and one or more acrylic acid monomers having reactive functional groups such as acrylic acid, methacrylic acid, acrylamide, N-methylol acrylamide, N-(methoxymethyl)acrylamide, allyl methacrylate, glycidyl acrylate, and glycidyl methacrylate. The thermosetting acrylic resin is crosslinked by utilizing the self-reactivity of the reactive functional groups or crosslinked by the reaction of the reactive functional groups with a curing agent such as an amine system, thereby curing.
[0058] (Polyurethane resin)
[0059] As the polyurethane resin, there can be mentioned a resin containing a residue of a polyfunctional isocyanate compound and a hydroxyl-containing compound. Specifically, there can be mentioned a resin containing an aromatic polyisocyanate such as tolylene diisocyanate, diphenylmethane isocyanate, or polymethylene polyphenylene polyisocyanate, an aliphatic polyisocyanate such as hexamethylene diisocyanate, or xylylene diisocyanate, or a mixture thereof, and a residue of a hydroxyl-containing compound such as a polyether polyol, a polyester polyol, a polyacrylate polyol, or a polycarbonate polyol. The polyurethane resin is crosslinked by reaction with a curing agent such as an isocyanate curing agent or a polyol curing agent, thereby curing.
[0060] (Unsaturated polyester resin)
[0061] Examples of the unsaturated polyester resin include dehydrated condensates of unsaturated dibasic acids such as maleic anhydride, fumaric acid, or itaconic acid, or compounds obtained by replacing a portion of unsaturated dibasic acids such as phthalic anhydride, isophthalic acid, or terephthalic acid with diols such as ethylene glycol, diethylene glycol, or propylene glycol, or compounds obtained by replacing a portion of unsaturated dibasic acids such as glycerol or pentaerythritol with polyols such as glycerol. The unsaturated polyester resin is crosslinked by reaction with a curing agent such as an isocyanate curing agent, thereby curing.
[0062] (Other thermosetting resins)
[0063] As phenolic resin, resins having more than 2 phenols (phenol, cresol, etc.) in the resin can be listed. For example, resins containing residues of phenols and formaldehydes or aldehydes can be listed. As phenolic resin, specifically, phenol novolac resin, cresol novolac resin, cresol naphthol formaldehyde polycondensate, triphenylmethane type multifunctional phenyl resin, etc. can be listed. In addition, as phenolic resin, phenol aralkyl resin can be listed. In addition, as melamine resin, alkyl etherified melamine resin and its substitution body can be listed. And then, as urea resin, ethylene urea resin, etc. can be listed. As thermosetting polyimide resin, resins containing residues of polyvalent carboxylic acid dianhydride and diamine compound, etc. can be listed. Specifically, thermosetting polyimide resins such as maleimide polymer, bismaleimide polymer, amino bismaleimide polymer, bismaleimide triazine polymer can be listed. These resins also cure via a cross-linking reaction with a curing agent.
[0064] (Preferred examples of thermosetting resins)
[0065] Among the above-mentioned thermosetting resins, the thermosetting resin preferably contains one or more selected from epoxy resins, acrylic resins, polyurethane resins, and unsaturated polyester resins, from the perspectives of many options for setting the glass transition temperature Tg to 30°C or above, fast curing reaction at high temperature, and easy preparation of a dispersed state of the curing agent. Among them, the thermosetting resin most preferably contains epoxy resin from the perspectives of economy, versatility, and operability.
[0066] <Preferred Examples of Adhesive Resins>
[0067] One of the preferred adhesive resins is a thermosetting resin containing at least one thermosetting resin selected from epoxy resin, acrylic resin, polyurethane resin and unsaturated polyester resin, and the total content (total mass of thermosetting resin / mass of adhesive resin × 100 (%)) is 20% by mass or more. If the adhesive resin contains at least 20% by mass of these thermosetting resins, the characteristics of these thermosetting resins can be fully utilized. Among them, the most preferred adhesive resin contains at least 50% by mass of epoxy resin from the perspective of economy, versatility and operability.
[0068] The adhesive resin may be composed of a thermosetting resin as long as it contains a thermosetting resin, or may contain organic or inorganic components other than the thermosetting resin. For example, it may contain a thermoplastic resin, an impact modifier such as core-shell rubber or natural rubber, a curing accelerator such as dimethyl urea, boron trifluoride, or triphenylphosphine, a known epoxy resin modifier, a reaction control agent (catalyst, etc.), a surfactant, a rust inhibitor, a lubricant, an antioxidant, a defoaming agent, or a coloring pigment, etc.
[0069] <Examples of Curing Agents>
[0070] Specifically, the curing agent includes amine-based, amide-based, imidazole-based, acid anhydride-based, phenol-based, catalyst-based curing agents, etc. In the present invention, for example, a crystalline curing agent that crystallizes at room temperature can be selected alone or in combination of two or more from the following specific examples.
[0071] (Amine curing agent)
[0072] The amine-based curing agent is not limited to the following, but examples thereof include aliphatic amines, aromatic amines, and guanidine compounds.
[0073] [Aliphatic amines]
[0074] The aliphatic amine is not limited to the following, but examples thereof include diethylenetriamine, triethylenetetramine, tetraethylenepentamine, meta-xylylenediamine, trimethylhexamethylenediamine, 2-methylpentamethylenediamine, isophoronediamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, 1,2-diaminocyclohexane, benzoylamine, methylcyclohexylamine, and diazabicycloundecene.
[0075] [Aromatic amines]
[0076] Examples of the aromatic amine include, but are not limited to, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenylsulfone (DDS), diethyltoluenediamine, trimethylenebis(4-aminobenzoate), polytetramethylene oxide-diparaaminobenzoate, methylaniline, and dimethylaniline.
[0077] [Guanidane compounds]
[0078] Examples of the guanidine compound include, but are not limited to, dicyandiamide (DICY, cyanoguanidine) and its derivatives, methylguanidine, ethylguanidine, propylguanidine, butylguanidine, dimethylguanidine, trimethylguanidine, phenylguanidine, diphenylguanidine, and tolylguanidine.
[0079] (Amide curing agent)
[0080] The amide curing agent is not limited to the following, but examples thereof include compounds obtained by adding an acid anhydride to an amine curing agent and hydrazide compounds.
[0081] [Hydrazide compounds]
[0082] Examples of the hydrazide compound include, but are not limited to, succinic acid dihydrazide, adipic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, p-hydroxybenzoic acid hydrazide, salicylic acid hydrazide, phenylaminopropionic acid hydrazide, and maleic acid dihydrazide.
[0083] (Imidazole curing agent)
[0084] Examples of the imidazole curing agent include imidazole-isocyanuric acid compounds, diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine (2MZ-AZINE), 1-cyanoethyl-2-ethyl-4-methylimidazole (CEMI), 2-ethyl-4-methylimidazole, and 2-undecylimidazole (C11Z).
[0085] (Anhydride curing agent)
[0086] Examples of the acid anhydride curing agent include, but are not limited to, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.
[0087] (Phenol-based curing agent)
[0088] The phenol-based curing agent is not limited to the following substances, but for example, phenol novolac resin, cresol novolac resin, phenol aralkyl resin, cresol aralkyl resin, naphthol aralkyl resin, biphenyl-modified phenolic resin, biphenyl-modified phenolic aralkyl resin, dicyclopentadiene-modified phenolic resin, aminotriazine-modified phenolic resin, naphthol novolac resin, naphthol-phenol co-condensation novolac resin, naphthol-cresol co-condensation novolac resin or allyl acrylic phenolic resin can be listed.
[0089] (Catalyst type curing agent)
[0090] The catalyst type curing agent is not limited to the following, but examples thereof include a cationic heat curing catalyst, a BF3-amine complex, and 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0091] Since the curing reaction rate of the adhesive resin composition film during hot pressing is fast, the adhesive resin composition film can be cured in a short time relatively easily, so the curing agent preferably includes one or more crystalline curing agents selected from amine curing agents, amide curing agents and imidazole curing agents. By using such a curing agent, the temperature of the adhesive resin composition coated electromagnetic steel sheet is set to be different from the heating temperature during hot pressing, so it is easy to control the heating rate during hot pressing. From the perspective of operation and versatility, the curing agent most preferably includes one or more selected from dicyandiamide (DICY), diaminodiphenyl sulfone (DDS) and diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine (2MZ-AZINE).
[0092] The laminated core 10 is formed by alternately laminating electromagnetic steel sheets 1 and adhesive insulating films 2. The laminated core 10 is composed of, for example, 600 electromagnetic steel sheets 1 and has an overall thickness of about 150 mm.
[0093] Here, the uppermost electromagnetic steel sheet 1 preferably has a convex portion 3 protruding in the lamination direction D. Thus, after forming the first laminated core 10 in a state where the lamination direction D is along the vertical direction in the mold, the electromagnetic steel sheet 1 at the lowermost layer of the second laminated core 10 formed on the first laminated core 10 is directly placed in contact with the electromagnetic steel sheet 1 at the uppermost layer of the first laminated core 10 in the same mold. Then, when the second laminated core 10 is pressed in the vertical direction, the lower surface of the electromagnetic steel sheet 1 at the lowermost layer of the second laminated core 10 only contacts the upper end of the convex portion 3 formed on the upper surface of the electromagnetic steel sheet 1 at the uppermost layer of the first laminated core 10. Therefore, the adhesive force at the contact portion between the upper end of the convex portion 3 and the lower surface of the electromagnetic steel sheet 1 at the lowermost layer of the second laminated core 10 can be made smaller than the self-weight of the lowermost first laminated core 10. Therefore, when mass-producing the laminated cores 10 in sequence in the mold, due to the action of gravity, the first laminated core 10 falls by itself. Thus, the first laminated core 10 and the second laminated core 10 can be separated and simply taken out of the mold individually. Therefore, the laminated core 10 can be manufactured with high production efficiency.
[0094] The conditions for generating the action of separating the first laminated core 10 from the second laminated core 10 by the action of gravity so that the first laminated core 10 falls by itself are as follows.
[0095] The number Q of the convex portions 3 formed on the upper surface of the uppermost electromagnetic steel sheet 1 for generating the above action, the contact area A (m 2 ) between the upper end of the convex portion 3 and the lower surface of the lowermost electromagnetic steel sheet 1, the relationship between the tensile strength σ (N / m 2 ) in the lamination direction of the laminated core 10 and the self-weight W (N) of the laminated core 10 can be expressed by the inequality σ×A×Q < W. At this time, the bonding area can be calculated using either the measured value obtained from the size of the manufactured core or the area in the equipment design, and it is preferable to use a preferred one.
[0096] <<Second Embodiment>>
[0097] Next, a method for manufacturing the laminated core 10 will be described.
[0098] The method for manufacturing a laminated core 10 formed by stacking a plurality of electromagnetic steel sheets 1 includes the following steps: a punching step of punching an electromagnetic steel strip coated with an adhesive insulating film 2 to form the electromagnetic steel sheets 1; a stacking step of stacking the electromagnetic steel sheets 1 and accommodating them in a mold after the punching step; a low-pressure bonding step of bonding adjacent electromagnetic steel sheets 1 to each other while heating the electromagnetic steel sheets 1 in the mold to a surface temperature of 60°C to 200°C under a pressure of 3.0 MPa or less to form a laminated core; and a removal step of removing the laminated core 10 from the mold after the low-pressure bonding step. Thus, the laminated core 10 can be integrally formed by pressurizing under relatively low temperature and relatively low pressure conditions, and the tensile strength in the stacking direction required for the laminated core 10 (e.g., 1 MPa) can be ensured. In addition, since the pressurizing force is low pressure, a special pressurizing device for pressurizing at high pressure is not required. Furthermore, since the core is at a low temperature, it can be removed from the mold at an early stage without taking time for natural cooling or accelerating cooling by a special cooling device, regardless of the cooling speed. Therefore, a method for manufacturing the laminated core 10 that can be manufactured with high production efficiency can be provided.
[0099] Hereinafter, each step will be described in detail.
[0100] (1) Preparation process
[0101] An electromagnetic steel strip coated with an adhesive insulating film 2 is prepared. Here, an adhesive resin that can achieve a tensile strength of 20 MPa in the stacking direction of the laminated core 10 after a complete reaction is used as the adhesive insulating film 2. As a result, as described below, even if the laminated core 10 is formed by pressurizing at low temperature and low pressure in the low-pressure bonding process, the tensile strength in the stacking direction of the laminated core 10 at the time of being taken out in the taking-out process can be set to 1 MPa or more, which is required for the laminated core 10 for motors.
[0102] (2) Punching process
[0103] Next, the electromagnetic steel strip coated with the adhesive insulating film 2 is punched out to form the electromagnetic steel sheet 1 (punching step).
[0104] Specifically, a hollow cylindrical die is set with its central axis along the vertical direction. A punch having a shape corresponding to the outer shape of the electromagnetic steel sheet 1 is set above the die for blanking. The electromagnetic steel strip is moved toward the die in the horizontal direction in a posture that the plate thickness direction of the electromagnetic steel sheet 1 is aligned with the vertical direction, so that it is located between the upper part of the die and the lower part of the punch. The punch is lowered to act on the electromagnetic steel strip, and the electromagnetic steel strip is blanked.
[0105] (3) Accommodation process
[0106] Next, after the punching step, the electromagnetic steel sheets 1 are stacked and housed in a mold (housing step).
[0107] Specifically, the electromagnetic steel sheet 1 formed by punching in the punching step falls into the die and is accommodated in the die.
[0108] In order to punch out the next electromagnetic steel sheet 1, the electromagnetic steel strip is moved in the horizontal direction. Then, the next electromagnetic steel sheet 1 is punched out through the punching process. The next electromagnetic steel sheet 1 falls into the die and is accommodated in the die in a state of being stacked on the previous electromagnetic steel sheet 1. By repeating these steps, the number of electromagnetic steel sheets 1 required for forming the laminated core 10 is stacked in the die.
[0109] (4) Low-pressure bonding process
[0110] Next, the electromagnetic steel sheets 1 in the mold are heated to a surface temperature of 60°C to 200°C (heating temperature) while being pressurized at 3.0 MPa or less, and the adjacent electromagnetic steel sheets 1 are bonded to each other to form the laminated core 10 (low-pressure bonding process). If the temperature is 200°C or less, the electromagnetic steel sheets 1 in the mold can be heated without making the equipment complicated or large. Here, as the adhesive insulating film 2 of the laminated core 10, an adhesive resin that can exert a tensile strength of 20 MPa in the lamination direction of the laminated core 10 after complete reaction is used, the laminated core 10 can be integrally formed by pressurization under relatively low temperature and relatively low pressure conditions, and the tensile strength in the lamination direction required for the laminated core 10 (for example, 1 MPa) can be ensured. In addition, since it is low pressure, a special pressurizing device for pressurizing at high pressure is not required. In addition, since it is low temperature, it can be taken out from the mold at an early stage without taking time for natural cooling or accelerating cooling by a special cooling device. The heating temperature may be set to 150°C or below, or 130°C or below. The pressure may be set to, for example, 0.1 MPa or above, 0.5 MPa or above, or 1.0 MPa or above. In addition, the pressure may be set to 2.0 MPa or below, or 1.5 MPa or below. It should be noted that in order to more reliably ensure the tensile bonding in the stacking direction of the laminated core, it is preferred to apply pressure, but pressure may not be applied (in which case the pressure is 0 MPa).
[0111] (4-1) Adhesion promotion step
[0112] Here, in the low-pressure bonding process, the electromagnetic steel sheet may be heated to a temperature of 100°C to 160°C at a heating rate of 0.5°C / s to 5.0°C / s (heating temperature), and maintained at this temperature for a holding time of 20 seconds to 120 seconds (adhesion promotion process). If the heating rate is too low, bonding requires a long time, and cost competitiveness decreases. In addition, even if the heating rate is too high, equipment for achieving a large heating rate becomes necessary. Therefore, the heating rate is preferably 0.5°C / s to 5.0°C / s. Thus, even in the process of heating to 60°C to 200°C under low pressure and low temperature conditions in the low-pressure bonding process, the bonding of adjacent electromagnetic steel sheets 1 can be further promoted. The heating temperature may be set to 150°C or less, or 130°C or less. The holding time may be set to 100 seconds or less, or 80 seconds or less. The heating rate may be set to 4.0°C / s or less, or 3.0°C / s or less. The temperature for starting the heating process in the adhesion promotion step is not limited, but may be set to a temperature 5° C. or more lower than the heating temperature, or may be set to room temperature (20° C.), for example.
[0113] The order of heating to the heating temperature in the low-pressure bonding process and heating and maintaining in the bonding promotion process is not limited. For example, heating to the heating temperature in the low-pressure bonding process may be performed after heating and maintaining in the bonding promotion process, or heating / maintaining in the bonding promotion process may be performed during the heating to the heating temperature in the low-pressure bonding process (at least a portion of the time from the start of heating to the reaching of the heating temperature).
[0114] The heating temperature in the low pressure bonding step and the heating temperature in the adhesion promotion step are not limited, but for example, the heating temperature in the adhesion promotion step may be set to be lower than the heating temperature in the low pressure bonding step.
[0115] In addition, cooling may be performed during the heating process to the heating temperature in the low-pressure bonding process or during the heating process to the heating temperature in the bonding promotion process, and heating and heating treatment may be performed twice or more in the low-pressure bonding process or the bonding promotion process. However, from the viewpoint of improving manufacturing efficiency, it is preferred to perform heating / heating treatment once in the low-pressure bonding process and the bonding promotion process without cooling.
[0116] (5) Removal process
[0117] Next, after the low-pressure bonding step, the laminated core 10 is taken out from the mold (taking out step). At this time, the tensile strength of the laminated core 10 in the lamination direction at the time of taking out is 1 MPa or more, which is required for the laminated core 10 for motor use. Therefore, a step of further heating to promote the bonding strength of the adhesive insulating film 2 is no longer necessary.
[0118] In this way, the laminated core 10 can be manufactured by a simple device, and the production tact time and the manufacturing lead time can be shortened.
[0119] (6) Reheating process
[0120] It should be noted that after the removal process, the laminated core 10 may be heated to 160° C. to 250° C. (reheating process). Thus, the tensile strength in the stacking direction can be further improved according to the requirements for the laminated core 10. When the adhesive insulating film is completely reacted, the tensile strength in the stacking direction measured at 25° C. is 20 MPa or more, so that the laminated core 10 having a higher tensile strength in the stacking direction than the conventional laminated core can be manufactured.
[0121] <Other Embodiments>
[0122] As mentioned above, although one embodiment is described in detail with reference to the drawings, the specific configuration is not limited to the above configuration, and various design changes and the like can be made.
[0123] The convex portion 3 may be formed, for example, by the following method: For example, instead of punching out by press working, the convex portion 3 may be formed by a method of making a convex portion with a punch.
[0124] In the laminated core 10 of the present embodiment, the electromagnetic steel sheets 1 and the adhesive insulating films 2 are alternately laminated, and the tensile strength in the lamination direction measured at 25°C after the complete reaction of the adhesive insulating films 2 is 20 MPa or more. Therefore, even at a relatively low temperature (60°C to 200°C), the adhesive strength (for example, 1 MPa) required for the laminated core 10 for the motor to be a product can be exhibited. Therefore, even if the electromagnetic steel sheets 1 are bonded to each other to form a laminated body (laminated core) without further heating, a high-strength laminated core 10 can be manufactured. Therefore, the laminated core 10 can be taken out of the manufacturing device in a low-temperature state, and the mechanism for high-temperature heating and cooling in the manufacturing device can be simplified, so the manufacturing device of the laminated core 10 can be miniaturized. Therefore, a laminated core 10 that can be manufactured with high production efficiency can be provided.
[0125] The manufacturing method of the laminated core 10 of the present embodiment is a method for manufacturing the laminated core 10 formed by stacking a plurality of electromagnetic steel sheets 1. The manufacturing method of the laminated core 10 includes the following steps: a punching step of punching out an electromagnetic steel strip coated with an adhesive insulating film 2 to form the electromagnetic steel sheets 1; a stacking step of stacking the electromagnetic steel sheets 1 and accommodating them in a mold after the punching step; a low-pressure bonding step of bonding the adjacent electromagnetic steel sheets 1 to each other while pressurizing the electromagnetic steel sheets 1 in the mold at a surface temperature of 60°C to 200°C to form a laminated core; and a removal step of removing the laminated core 10 from the mold after the low-pressure bonding step. Thus, the laminated core 10 can be integrally formed by pressurizing under relatively low temperature and relatively low pressure conditions, and the tensile strength in the stacking direction (e.g., 1 MPa) required for the laminated core 10 can be ensured. Furthermore, since the pressurizing force is low pressure, a special pressurizing device for pressurizing at high pressure is not required. Furthermore, since the temperature is low, it can be taken out from the mold at an early stage without taking time for natural cooling or accelerating cooling by a special cooling device. Therefore, a method for manufacturing the laminated core 10 that can be manufactured with high production efficiency can be provided.
[0126] Example
[0127] (Tensile strength test in stacking direction)
[0128] The laminated cores produced under different manufacturing conditions were tested for measuring the tensile strength in the lamination direction. A fully automatic metal tensile testing machine manufactured by Shimadzu Corporation was used for the test.
[0129] Figure 4 This is a table showing the relationship between the test specimens, test conditions, and test results of the tensile adhesion test.
[0130] exist Figure 4In the table, from the left column, "No." indicates the number of the test body, "Example or Comparative Example" indicates the difference between the example and the comparative example, "Heating temperature" indicates the temperature at which the stacked plurality of electromagnetic steel sheets are heated in the low-pressure bonding process in the process of forming the laminated core in °C, "Pressure" indicates the pressure at which the stacked plurality of electromagnetic steel sheets are pressed in the low-pressure bonding process in the process of forming the laminated core in MPa, "Heating rate" indicates the rate at which the temperature is increased from the heating start temperature (room temperature (20 °C)) to the heating temperature in the bonding promotion process in °C / s, and "Amount of temperature increase" indicates the amount of temperature increase from the heating start temperature (room temperature (20 °C)) to the heating temperature in the bonding promotion process in °C. The temperature range from the heating temperature to the heating temperature (maximum reaching temperature) (= heating temperature (℃) - 20 (℃)), "holding time" represents the holding time at the temperature of 60℃ to 120℃, which is the heating temperature, in seconds, "reheating temperature" represents the temperature reached by reheating after being taken out of the mold, and "90℃ stacking direction tensile strength" represents the case where the stacking direction tensile strength of the manufactured laminated core at 90℃ is 1MPa or more as "B", the case where the stacking direction tensile strength of the manufactured laminated core at 90℃ is 3MPa or more as "A", and the case where the stacking direction tensile strength is less than 1MPa as "C". It should be noted that in all test conditions, the heating temperature of the low-pressure bonding process and the heating temperature of the bonding promotion process are at the same temperature.
[0131] The contents of the test are as follows.
[0132] The laminated core is set as a stator core used as a stator for a motor.
[0133] The electromagnetic steel sheet used for manufacturing the laminated core was set to 25HX1300 (a non-oriented electromagnetic steel sheet with a low iron loss and high magnetic flux density and a sheet thickness of 0.25 mm).
[0134] The laminated core is made of 600 stacked electromagnetic steel plates.
[0135] The lamination thickness (length along the lamination direction D) of the laminated core was set to 150 mm.
[0136] The laminated core is formed by stacking a plurality of electromagnetic steel sheets in a mold at room temperature (20°C) as the starting temperature for heating. Figure 4 The specified pressure shown in the figure is applied while Figure 4 The specified temperature rise rate shown in the figure is heated to the specified surface temperature ( Figure 4 The heating temperature shown in = heating temperature) is maintained at this temperature. Figure 4 The prescribed time shown in .
[0137] The test body is set to be Figure 1 The test body is cut out in a cubic shape as indicated by the dotted line in FIG. The size of the test body along the stacking direction D is set to 45.0 mm in length×3.6 mm in width×12.25 mm in height.
[0138] The 90°C lamination direction tensile strength is set as the value obtained by dividing the maximum load when the tensile load is gradually increased in the longitudinal direction of the test body heated to 90°C by the cross-sectional area of the test body while the two ends of the test body in the longitudinal direction are held by the chucks of the tensile tester. It should be noted that the electromagnetic steel sheets constituting the test body are bonded to the entire surface by an adhesive insulating film.
[0139] The adhesive insulating film (adhesive coating) used is set to be an adhesive resin whose tensile strength in the lamination direction at 25°C after complete reaction is 20 MPa or more, or an adhesive resin whose tensile strength in the lamination direction at 25°C after complete reaction is 14 MPa under the same conditions. It should be noted that the tensile strength in the lamination direction at 25°C after complete reaction of the adhesive resin is measured in advance by the same method as the measurement of the tensile strength in the lamination direction at 90°C described above.
[0140] Specifically, in the examples of No. 1, 4, 5, 8, 9, 11-18, as the thermosetting resin, 44 parts by mass of a phenol novolac epoxy resin (PPN201 manufactured by Nippon Kayaku Co., Ltd.), 12 parts by mass of a cresol novolac epoxy resin (YDCN-700-10 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), 10 parts by mass of a trifunctional epoxy resin (EP-3950E manufactured by ADEKA Co., Ltd.), 30 parts by mass of a quadrifunctional epoxy resin (YH-404 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), and 4 parts by mass of a bisphenol A epoxy resin (Epikote manufactured by Mitsubishi Chemical Co., Ltd.) were used, and as the thermoplastic resin, a phenoxy resin (NIPPON STEEL Chemical & Material Co., Ltd., YPS-007A30) 40 parts by mass (based on thermosetting resin), core-shell rubber 10 parts by mass (based on thermosetting resin), DICY 12 parts by mass as a curing agent (based on thermosetting resin). The tensile strength of the adhesive resin in the lamination direction at 25°C after complete reaction is 24 MPa.
[0141] In the example of No. 2, as the thermosetting resin, 44 parts by mass of a phenol novolac epoxy resin (PPN201 manufactured by Nippon Kayaku Co., Ltd.), 12 parts by mass of a cresol novolac epoxy resin (YDCN-700-10 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), 10 parts by mass of a trifunctional epoxy resin (EP-3950E manufactured by ADEKA Co., Ltd.), 30 parts by mass of a tetrafunctional epoxy resin (YH-404 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.), and 4 parts by mass of a bisphenol A epoxy resin (Epikote manufactured by Mitsubishi Chemical Co., Ltd.) were used, and as the thermoplastic resin, a phenoxy resin (NIPPON STEEL Chemical & Material Co., Ltd., YPS-007A30) 40 parts by mass (based on thermosetting resin), core-shell rubber 10 parts by mass (based on thermosetting resin), DDS 41 parts by mass as a curing agent, and DCMU 2 parts by mass (based on thermosetting resin). The tensile strength of the adhesive resin in the lamination direction at 25°C after complete reaction is 83 MPa.
[0142] For the examples of No. 3, 6, and 10, 56 parts by mass of phenol novolac epoxy resin (PPN201 manufactured by Nippon Kayaku Co., Ltd.) and 44 parts by mass of tetrafunctional epoxy resin (YH-404 manufactured by NIPPON STEEL Chemical & Material Co., Ltd.) were used as thermosetting resins, 33 parts by mass of phenoxy resin (YP-50 manufactured by NIPPONSTEEL Chemical & Material Co., Ltd.) as thermoplastic resins (based on the thermosetting resin), 5 parts by mass of core-shell rubber (based on the thermosetting resin), 12 parts by mass of DICY and 5 parts by mass of DCMU (based on the thermosetting resin) as curing agents were used. The tensile strength of the adhesive resin in the lamination direction at 25° C. after the complete reaction was 14 MPa.
[0143] The heating temperature (surface temperature) was selected from 200° C., 120° C., and 60° C. and combined with other conditions.
[0144] The pressure can be selected from 1.0 MPa, 0 MPa, and 3.0 MPa and combined with other conditions.
[0145] The heating rate can be selected from 3°C / s, 5°C / s, 0.15°C / s, 10°C / s and 0.1°C / s and combined with other conditions.
[0146] The temperature range, that is, the temperature increase amount, from room temperature (20° C.) to the heating temperature (= heating temperature) is selected from 100° C., 40° C., and 180° C. and combined with other conditions.
[0147] The holding time for holding at a temperature of 60° C. to 200° C. as a heating temperature is selected from 20 seconds, 0 seconds, 120 seconds, and 200 seconds, and is combined with other conditions.
[0148] The temperature at which the sample is heated again after being taken out of the mold, i.e., the reheating temperature, is selected from no reheating, 160° C., or 250° C. and combined with other conditions.
[0149] The tensile strength in the stacking direction was tested. If the tensile strength in the stacking direction was 1 MPa or more, it was considered acceptable. If the tensile strength in the stacking direction was less than 1 MPa, it was considered unacceptable. Figure 4 In the example, the qualified case is represented by "A" or "B", and the unqualified case is represented by "C".
[0150] The results of the test are that Figure 4 As shown in , Nos. 1, 2, 4, 5, 8, 9, 11 to 18 as examples were acceptable, and Nos. 3, 6, and 10 as comparative examples were unacceptable.
[0151] Thus, it was confirmed that if the tensile strength in the lamination direction D measured at 25°C after the complete reaction of the adhesive insulating film 2 is set to 20 MPa or more, even when the mold is pressurized at low temperature and low pressure, the tensile strength in the lamination direction at the time of removal from the mold (90°C) can be ensured to be 1 MPa or more. In addition, since the tensile strength in the lamination direction of the laminated core of the embodiment is 20 MPa or more at 25°C after the complete reaction of the adhesive insulating film, a laminated core having a higher tensile strength in the lamination direction than before is obtained. It should be noted that the tensile strength in the lamination direction at 25°C was confirmed to be 20 MPa or more by using a test piece cut out from a part of the manufactured laminated cores of the embodiment for measurement.
[0152] Explanation of symbols
[0153] 1Electromagnetic steel plate
[0154] 2. Adhesive insulation film
[0155] 3 convex parts
[0156] 10 laminated core
[0157] D stacking direction
Claims
1. A laminated core, wherein: Magnetic steel sheets and adhesive insulating films are alternately laminated. After the adhesive insulating film has completely reacted, the tensile adhesive strength in the lamination direction when measured at 25° C. is 20 MPa or more.
2. The laminated core according to claim 1, wherein: The uppermost electromagnetic steel sheet has a convex portion protruding in the stacking direction.
3. A method for manufacturing a laminated core, which is a method for manufacturing a laminated core formed by laminating a plurality of electromagnetic steel sheets, comprising the following steps: a punching step of punching an electromagnetic steel strip coated with an adhesive insulating film to form the electromagnetic steel sheet; After the punching step, a step of stacking the electromagnetic steel sheets and accommodating them in a mold; A low-pressure bonding step of heating the electromagnetic steel sheets in the mold to a surface temperature of 60° C. to 200° C. while applying a pressure of 3.0 MPa or less, and bonding adjacent electromagnetic steel sheets to each other to form a laminated core; and After the low-pressure bonding step, a removing step of removing the laminated core from the mold is performed.
4. The method for manufacturing a laminated core according to claim 3, wherein: The low-pressure bonding step includes the following bonding promotion step: heating to a temperature of 100° C. to 160° C. at a heating rate of 0.5° C. / s to 5.0° C. / s, and maintaining at the temperature for 20 seconds to 120 seconds. 5 . The method for manufacturing a laminated core according to claim 3 , further comprising, after the taking-out step, a reheating step of heating the laminated core to 160° C. to 250° C. 6 . The method for manufacturing a laminated core according to claim 3 , wherein in the low-pressure bonding step, the electromagnetic steel sheets in the mold are pressurized at 0.1 MPa or more.
Citation Information
Patent Citations
Apparatus for manufacturing laminated iron core
JP2009297758A
Method and apparatus for manufacturing laminate
JP2010274625A
Manufacturing method of laminated motor core, and holding jig for manufacturing laminated motor core
JP2021129453A
Manufacturing method of laminated core
JP2022000888A
Component mounting device
JP2022143134A